IMPLEMENTASI PROCUREMENT KARYAWAN PADA PT ASIA PACIFIC FIBERS TBK KALIWUNGU - Anita - Sabrina; Endang - Sulistyani (Politeknik Negeri Semarang, 2016)
The aims of this study is to identify thetask of Human Resources Departmentand the implementation of employeesprocurement at PT Asia Pacific Fibers TbkKaliwungu. This final project usesdescriptive qualitative method. The datafor this final project are qualitative andquantitative and taken from primary andsecondary data source. Data were collectedby doing observation, interview andliterature study. The result of the studyshows that employees procurement ofPT Asia Pacific Fibers Tbk Kaliwungurefers to the job description, jobspecification, job evaluation, jobexpansion, and job requirement. There are4 processes of employees procurement atPT Asia Pacific Fibers Tbk Kaliwungu,namely forecasting and filing needs ofemployees, recruitment, selection,placement and induction. Implications ofthe discussion employees procurement at PTAsia Pacific Fibers Tbk Kaliwungu are inaccordance with the theories. It's just theprocess of selection, employees selectionsequence which is different, but it has thesame core. PT Asia Pacific Fibers TbkKaliwungu has its own policy in relation tothe procurement of employees. In theselection process, PT Asia Pacific Fibers TbkKaliwungu not perform medical tests. This isbecause at the beginning of the job opening,does the company has put a condition thatcandidate should attach a health certificatefrom a doctor, so the company does notperform medical tests.